The Stability of Fluctuation Immigration Effect on Two Species Prey-Predator System with Holling Type II Functional Response - Jawdat Alebraheem, GhassanEzaldeen, Israa Names, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper examines the fluctuation immigration effect on the dynamic behavior of the prey-predator system, with Holling type II functional response. The mathematical technique to formulate and combine the effect of fluctuating immigration with the prey-predator system was provided. the result of this combined is a non-autonomous system. In order to convert it to an autonomous system, we propose an approximated technique for facilitating mathematical analysis. This system has been examined for local and global stability. as well, it is tested using Kolmogorov criteria in order to verify the susceptibility to coexistence and extinction.